O ensino no património : sensibilizar para preservar, conservar e restaurar - Frade, Marta (2018)
This essay aims at sharing the experience garnered from the work developed with second and third grade students (corresponding to 11th and 12th grades respectively, in the Portuguese 12-year school system) from Escola Profissional de Recuperação do Património de Sintra (vocational education for cultural heritage conservation) enrolled on the course Conservation and Restoration Technician in the field of Plaster over the years. Specifically, the work developed within the modules Theory and Practice in Conservation and Restoration and Workplace Training, through the completion of theoretical practical activities and training in workplace directly integrated into the scope of our heritage, thus showing that the practical training motivates and prepares the students for a future job